PENGARUH GAYA KEPEMIMPINAN , IKLIM ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DALAM ORGANISASI PADA RSIA YADIKA KEBAYORAN LAMA - Ester Clara Butar-butar; Guston Sitorus (Jurnal Satya Mandiri Manajemen dan Bisnis, 2015)
Optimal performance can be obtained if the spirit and passionate employees to do the job and be able to achieve the set targets . Improved performance of the employees can not be separated from some of the factors that can affect the performance of the employee , among other leadership, organizational climate , and competence. So the purpose of this study was to determine the effect of Leadership , Organizational Climate , and competence on Employee Performance in Organization In Yadika RSIA Kebayoran Lama . Design research is quantitative associative , while the data collection method is a survey using a questionnaire . The analysis of data using multiple linear regression , and the result is that the style of leadership , organizational climate , and the competence of either jointly or partially positive effect on the performance of employees in RSIA Yadika Kebayoran Lama.